2023
DOI: 10.7589/jwd-d-21-00178
|View full text |Cite
|
Sign up to set email alerts
|

Using Wildlife Rehabilitation and Postmortem Data to Identify Key Causes of Morbidity and Mortality Impacting the Health and Welfare of Free-Living Wild Animals in Canada

Abstract: The health and welfare of wild animals are of increasing concern, yet there are very few large-scale data syntheses examining how causes of wildlife morbidity and mortality vary across time, space, and taxa. Records for 18,540 animals submitted to the Canadian Wildlife Health Cooperative (CWHC) (2009–19) and 144,846 animals admitted to 19 wildlife rehabilitation centers (WRCs) (2015–19) were evaluated to 1) identify the main causes of morbidity and mortality for Canadian wildlife and 2) assess the utility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Traumatic injury is a common finding in animals presented to WRCs internationally, with ‘trauma’ accounting for 38.1% of WRC admissions in New York State [ 33 ]. A recent study of data both from Canadian WRCs and submissions to a national pathology service found the main reasons for admissions in both instances, 44% and 48% of admissions, respectively, to be trauma [ 69 ], illustrating the importance of trauma on both WRC admissions and truly wild populations. In this study, as in others, trauma in birds is frequently reported to be a more significant cause of morbidity and mortality than in mammals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Traumatic injury is a common finding in animals presented to WRCs internationally, with ‘trauma’ accounting for 38.1% of WRC admissions in New York State [ 33 ]. A recent study of data both from Canadian WRCs and submissions to a national pathology service found the main reasons for admissions in both instances, 44% and 48% of admissions, respectively, to be trauma [ 69 ], illustrating the importance of trauma on both WRC admissions and truly wild populations. In this study, as in others, trauma in birds is frequently reported to be a more significant cause of morbidity and mortality than in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors cite ‘collision with vehicles’ (‘hit by car’, ‘road traffic collision’, ‘vehicle impact’, etc.) as a common anthropogenic cause of trauma, accounting for between 11% of admissions across all species in a Canadian study [ 69 ], 34.7% in an Australian study [ 16 ], and 30% in Tasmania [ 38 ]. Of the known causes for rescue in New South Wales, Australia, ‘collisions with vehicles’ were the most common across all taxonomic groups, accounting for 24.3% of all cases, 20.5% for birds, and 33.5% for mammals [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations